PROFIL KEMAMPUAN BERPIKIR KRITIS MURID PADA MATERI GERAK BENDA KELAS VIII SMP DI BANGKALAN BERDASARKAN INDIKATOR ENNIS - Abdullah, Muhammad Hafizh; Setiawan, Beni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to map the profile of students’ critical thinking skills on the topic of motion at the junior high school level using a descriptive and empirical approach. The background of this research is based on the importance of critical thinking skills in science learning, as well as the gap between curriculum demands and actual classroom conditions. The study employs a quantitative descriptive design with a survey approach. The research subjects consist of 31 eighth-grade students who have studied the topic of motion. The instrument used is a multiple-choice test designed to measure five indicators of critical thinking, namely elementary clarification, basic support, inference, advanced clarification, and strategies and tactics. Data are analyzed using descriptive statistics, including mean, median, mode, standard deviation, as well as minimum and maximum values. The results of the study indicate that the average students’ critical thinking score is 65.4, which falls into the moderate category. Indicator-based analysis shows that the highest achievement is in the basic support indicator (71.0), followed by inference and advanced clarification (68.8), elementary clarification (63.4), and the lowest in strategies and tactics (54.8). These findings suggest that students are relatively capable of using information and drawing conclusions, but still have weaknesses in designing problem-solving strategies. Gender-based analysis shows no significant difference in the overall scores, although there are slight variations across certain indicators.